Lower cognitive scores among toddlers in birth cohorts with acute respiratory illnesses, fevers, and laboratory‐confirmed influenza. Issue 1 (14th September 2021) - Azziz‐Baumgartner, Eduardo; Gonzalez, Rosalba; Davis, William; Calvo, Arlene; Olson, Natalie; Grant, Lauren; Hess‐Holtz, Morgan; Veguilla, Vic; Rauda, Rafael; Kaydos‐Daniels, Susan Cornelia; Sosa, Nestor; Aedo Ruíz, Evelina I.; et al.
Abstract: Background: We established cohorts to assess associations between viral influenza and cognitive development to inform the value proposition of vaccination. Methods: From 2014 through 2017, we called women seeking care at four prenatal clinics in Panama and El Salvador to identify acute respiratory illnesses (ARIs). Within 2 weeks of childbirth, mothers were asked to enroll their neonates in the cognitive development study. Staff obtained nasopharyngeal swabs from children with febrile ARIs for real‐time reverse transcription polymerase chain reaction (rtPCR) detection of viral RNA. Toddlers were administered Bayley developmental tests at ages 12 and 18–24 months. We used multilevel linear regression to explore associations between Bayley scores, ARIs, fever, and laboratory‐confirmed influenza, controlling for maternal respiratory or Zika illnesses, infant influenza vaccination, birth during influenza epidemics, and the number of children in households. Results: We enrolled 1567 neonates of which 68% (n = 1062) underwent developmental testing once and 40% ( n  = 623) twice. Children with previous ARIs scored an average of 3 points lower on their cognitive scores than children without ARIs ( p  = 0.001). Children with previous fevers scored an average of 2.1 points lower on their cognitive scores than afebrile children ( p  = 0.02). In the second year, children with previous laboratory‐confirmed influenza scored 4 points lower on their cognitive scores than children without influenza ( p  = 0.04, after controlling for first Bayley cognitive scores). Conclusions: ARIs and fever during infancy were associated with lower Bayley scores at 12 months, and laboratory‐confirmed influenza was associated with lower cognitive scores at 24 months suggesting the potential value of vaccination to prevent non‐respiratory complications of influenza.